2011
DOI: 10.1080/08911762.2011.558811
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Provision of Online Channel Functions on Exporting Channel Performance: The Moderating Effect of International Experience

Abstract: The purpose of this research is to investigate the effect of the provision of two online channel functions on exporting channel performance, using international experience as a moderating variable. The study setting is Taiwan. The results confirm that the provision of online communication and transaction functions can increase exporting channel performance. Moreover, international experience can better facilitate the effect of the provision of online transaction functions on exporters' channel performance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…1 • 103-128 In three of the countries, strong evidence can be found of e-sales being positively associated with the probability of exporting. This suggests there are benefits to online sales as a channel of distribution that can reach foreign customers and is consistent with the findings of similar studies (such as Wang et al, 2011). However, results for the remaining countries where no such evidence was found seem more in line with research that has found no evidence of an effect on export performance (Morgan-Thomas, 2009) or has emphasised that using online sales as an alternative to physical presence on a foreign market does not lead to higher performance (Sinkovics et al, 2013).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1 • 103-128 In three of the countries, strong evidence can be found of e-sales being positively associated with the probability of exporting. This suggests there are benefits to online sales as a channel of distribution that can reach foreign customers and is consistent with the findings of similar studies (such as Wang et al, 2011). However, results for the remaining countries where no such evidence was found seem more in line with research that has found no evidence of an effect on export performance (Morgan-Thomas, 2009) or has emphasised that using online sales as an alternative to physical presence on a foreign market does not lead to higher performance (Sinkovics et al, 2013).…”
Section: Resultssupporting
confidence: 91%
“…In the case of service firms, having a website does not seem to be relevant for the export propensity, whereas e-sales are, but only in 2 out of 8 countries. In Poland and UK, the coefficient of the broadband-Internet-enabled employees' variable is highly statistically significant and positive, even after controlling for firm's human capital, which seems to be in line with the benefits of access to Internet for internationalisation (Clarke, 2008) that can range from new information and thus new market knowledge (Mathews and Healy, 2008), to easier communication with customers and customer support (Morgan- Thomas, 2009, Wang et al, 2011.…”
Section: Resultsmentioning
confidence: 76%
“…placing orders, making payments, and generating sales) will have a stronger impact on performance when firms has less international experience, while providing online communication functions (e.g. collecting foreign customer information and communicating with them) will have a stronger impact on performance when firms have more international experience (Wang et al, 2011).…”
Section: Consequences and Outcomes Of Internet-enabled Internationalimentioning
confidence: 99%
“…Previous studies on buyer-seller relationships declare that channel functions such as delivery assistance, information provision, monitoring and cost savings are positively related to performance (Kalwani and Narayandas, 1995;Lusch and Brown, 1996;Noordewier et al, 1990;Schiele, 2007;Wang et al, 2011). Nomological validity is tested using five items of construct operating performance, based on Frecka's (1988) performance evaluation perspective.…”
Section: Nomological Validitymentioning
confidence: 99%